2018
DOI: 10.3906/bot-1802-9
|View full text |Cite
|
Sign up to set email alerts
|

Moscow Digital Herbarium, an online open access contribution to the flora of Turkey, with a special reference to the type specimens

Abstract: Massive imaging of herbarium collections is performed only in a few countries, leading to disproportions in geographical coverage of the world's flora across virtual herbaria. The Moscow University Herbarium (MW) digitised all Asian collections in 2016-2017 and published them online at https://plant.depo.msu.ru/, including 3283 specimens from Turkey. These collections include important historical gatherings by P.E. Boissier, C. Haussknecht, and T. Kotschy and recent collections by the Moscow University staff m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The relevant literature was used for typification (Ali, 1972;Turland and Jarvis, 1997;Seregin et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The relevant literature was used for typification (Ali, 1972;Turland and Jarvis, 1997;Seregin et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were collected from the Anamurdistrict (around Çukurabanoz village), Mersin province in the south of Turkey by Ömer ÇEÇEN(Figure1,2).The collected specimens were identified using the relevant literature (Ekim, 1982;Duman, 2000;Dirmenci, 2012;Seregin et al, 2018;Özhatay et al, 2019Özhatay et al, , Aksoy et al, 2020 and compared with materials stored in herbaria ANK, B, BM, E, EGE, GAZI, HUB, ISTE, ISTO, K, LE, MA, W, and WU (see http://sweetgum.nybg.org/science/ih/ for the indicated acronmys), as well as with our own herbarium specimens.…”
Section: 1plant Materialsmentioning
confidence: 99%
“…Specimens were collected from the Seydikemer district (Pinara Ancient City), Muğla province in southwestern Turkey (Figure 2, Appendix). The collected specimens were identified using the relevant literature (Ekim, 1982;Duman, 2000;Dirmenci, 2012;Seregin et al, 2018;Özhatay et al, 2019) and compared with materials stored in herbaria which the acronyms are indicated as ANK, B, BM, E, EGE, GAZI, HUB, ISTE, ISTO, K, LE, MA, W, and WU, as well as with our own herbarium specimens in the Balıkesir University Herbarium (see Appendix).…”
Section: Plant Materialsmentioning
confidence: 99%